Uso de marcadores y selección de gametos para el mejoramiento simultáneo de caracteres múltiples de frijol (Phaseolus vulgaris L.) para Mesoamérica y el Caribe - Singh, Shree P. (1998)
Use of molecular markers and gamete selection for simultaneous improvement of multiple characters in the common bean (Phaseolus vulgaris L.) for middle America and the Caribbean. The objective is to describe the basic requirements and alternative selection methods for simultaneous improvement of maximum number of agronomic characters in the shortest time possible. This strategy includes: (1) deterrnination of the importance and priorities of bean production problems in the region, (2) definition of objectives and priorities of breeding, (3) identification and use of reliable parental sources considered to be donors of necessary genes, (4) development of multiple-parent crosses with large number of pollinations to produce sufficient seed of each cross, (5) evaluation and selection for currently available markers (e.g., for zabrotes, bean common mosaic, bean golden mosaic, rust, anthracnose, apion, common bacterial blight, etc.) from hybridization, (6) alternative selection methods such as gamete selection and single seed descendants (GS-SSD), gamete and pedigree selection using markers (GS-PUM), gamete selection and agronomic evaluation and selection of families in early generations (GS-AEF), or a combination and integration of the GS-PUM and GS-AEF methods; and (7) seeking genuine and direct collaboration and integration in all activities of researchers from different disciplines, institutions, countries and the entire region at key sites foro reliable evaluation of bean nurseries in order to carry out simultaneous selection for a maximum number of agronomic traits.